Abraham w Pochwale Ojców (Syr 44,19-21) - Piwowar, Andrzej (Collectanea Theologica, 2019)
The article is devoted to the presentation of Abraham in the Greek text of the Praise of the Fathers (Sir 44:19-21). Only 13 verses are devoted to the patriarch, but his description carries a wealth of theological meaning. Sirach presents Moses as an ideal and a model to follow for himself, his contemporaries and all believers (cf. Sir 44:19b). First of all, he emphasizes Abraham’s moral and religious perfection (cf. Sir 44:20), which manifested itself in his abiding by the Law (cf. Sir 44:20a) and respecting the covenant with God, reflected primarily through the sign of circumcision (cf. Sir 44:20bc). Abraham was completely loyal to God and proved his loyalty during a trial (cf. Sir 44:20d). Sirach stresses especially one’s attitude to the covenant with God as the most important aspect of a believer’s life; in this respect Abraham should be a model to emulate. In the final part of the fragment the sage focuses on the result of Abraham’s faithfulness to God. The Lord promised him numerous offspring (cf. Sir 44:21cd) and an inheritance encompassing the whole Earth (cf. Sir 44:21e-g). Sirach emphasizes the special position of Abraham’s offspring among the nations (the latter will receive blessings through the former; cf. Sir 44:21b). What is more, Abraham’s offspring will be elevated over other nations (cf. Sir 44:21d). What is particularly noteworthy in Sirach’s reinterpretation of Abraham is that the patriarch respected the Law and that the sage attributed Messianic features to him.